Deficit metrics in Australian Indigenous education: through a media studies lens. Issue 2 (4th March 2022) - McCallum, Kerry; Ryan, Tess; Caffery, Jo
ABSTRACT: Journalistic news values and digital technology align with education policy and practice to construct a narrow world of Indigenous educational achievement and contribute to a discourse of negativity, failure and disempowerment. Digital technologies have enabled the online publication of educational performance that is a valuable source of news for journalists and editors. In this virtual world, Indigenous students are numerically ranked and publicly compared to their 'mainstream' peers. Despite significant criticism of the educational trend towards high-stakes testing and league tables there has been little investigation into the role of news media in the reporting of Australia's National Assessment Program – Literacy and Numeracy (NAPLAN). This article takes a media studies lens to examine the measurement and comparison of Indigenous school performance through the online publication of NAPLAN results and the My School website. A textual analysis of 143 news reports about Australian Indigenous students' NAPLAN results over an eight-year period from 2010 to 2017 found that Australia's news media told the story of Indigenous educational performance through a language of measurement and failure. This focus on deficit metrics fails to question the underlying assumptions of educational testing and comparison and perpetuates a discourse of deficit in Indigenous education.